The effect of fishbone fiber and rice husk ash additive on the mechanical properties of normal concrete. Issue 1 (September 2020) - Damayanti, S; Aulia, T B; Hayati, Y
Abstract: Concrete is a material that strong in holding compression force but weak in holding tension force so reinforcement is needed to prevent cracks in the pull region. Tuna bone fibers work as reinforcement, which is expected to overcome the problem of brittle concrete and produce ductile concrete. To improve concrete performance, fibers and additives are used. Tuna bone fibers and rice husk ash additives were selected to be able to utilize local natural materials. The purpose of this study is to examine the mechanical properties of normal concrete, which include compressive strength and tensile strength, by adding fiber and ash additives. The percentage of fibers added is 0%, 0.5%, 1%, and 1.5% of volume of concrete, and the percentage of additives is 0%, 10%, and 15% of weight of cement. Compression tests were performed to a total of 90 pieces of objects at 7, 28, and 56 days of age. Split tensile tests were performed to a total of 60 pieces of objects at the 28 and 56 days of age. The maximum compressive strength at 7, 28, and 56 days of age are 31.45 MPa, 36.81 MPa, and 41.16 MPa, respectively which were produced by variation BNS1 (BN+fiber 0.5%). The maximum tensile strength at 28 and 56 days of age are 4.08 MPa and 4.12 MPa; respectively which were produced by variation of BNS2 (BN+fiber 1%). All specimens at 7, 28, and 56 days of age produce concrete compressive strength on average 20 MPa of concrete above so that it is categorized into structural concrete.